Pigment-based biosensors for environmental monitoring - Shivangini Desai; Sonal Desai (Talanta Open)
Environmental pollution is progressively escalating owing to an increase in population and industrialization. Various industrial wastes are discharged into the water, soil, and air. Consequently, there is an urgent need to monitor the levels of these pollutants in the environment, as they pose a threat not only to human health, but also to the ecosystem, affecting all organisms. A biosensor detects biological or chemical processes by generating signals proportional to the analyte concentration in the reaction. Biosensors are utilized to monitor Biochemical Oxygen Demand (BOD), pesticides, phenols, heavy metals, and polluting gases. Pigment-based biosensors facilitate colorimetric and visual detection without the need for complex instrumentation. These biosensors can produce a response either because the analyte reacts directly with the pigment or through the analyte interacting with a genetic pathway that leads to pigment production, resulting in colour change. Through the genetic engineering of microorganisms to produce specific pigments, specific heavy metal detection can be achieved. This study examines the applications of pigment-based biosensors in the environmental monitoring of various pollutants, including heavy metals and pesticides, in contrast to conventional detection techniques. It also explores the recent advancements and limitations.